Help overcoming pain early, a brief person-centred intervention for adolescents with chronic pain in a school setting, may improve symptoms of insomnia - Wallbing, Ulrika; Nilsson, Stefan; Lundberg, Mari; Wigert, Helena; Kemani, Mike K. (Frontiers in Pain Research, 2023)
Introduction and aims Chronic pain and symptoms of insomnia affect large numbers of adolescents and early interventions are prioritized. The aim of the current study was to evaluate potential secondary effects of the intervention, Help Overcoming Pain Early (HOPE), on symptoms of insomnia and self-rated health. Methods The study included non-randomized aggregated data from the active and control conditions in a previously conducted randomized controlled trial evaluating the efficacy of HOPE, after the participants in the control condition also had received the intervention. Symptoms of insomnia were assessed with the Minimal Insomnia Symptom Scale and self-rated health was assessed with one item, at the start of the intervention, post intervention, and at a six-month follow-up. Baseline variables included age, gender, pain localization, pain impact, school absence and symptoms of depression (assessed with the Center for Epidemiological Studies Depression Scale for Children). Inferential analyzes were performed using Linear Mixed Models (LMM). Effect sizes were evaluated by calculating Cohen's d. Results There were statistically significant improvements in symptoms of insomnia at the six-month follow-up, and statistically significant improvements in self-rated health at the end of the intervention and at the six-month follow-up. Effect sizes were small across outcomes and assessments. Discussion and conclusion Results illustrated significant but small improvements in symptoms of insomnia and self-rated health in adolescents with chronic pain following the HOPE intervention. Although caution is needed when assessing the findings, results illustrate the potential utility of an accessible brief early intervention in a school context.